O imaginário do revisor de textos nos ritos genéticos editoriais - Sousa, Luciana Rugoni (2015)
For many people, text proofreading is something purely exclusively technical, in virtue of their disregard for the complexity of the proofreading processes, such as suggestions made on another person’s text: which has a normative dimension, and thus ideological implications. In this context, we analyze discourses about reganding proofreading, materialized in texts collected from different forums. The goal is to understand the dynamics in which certain discourses are told (or untold), and how they are constructed by others in the traces where emerges a figure of the reviewer. Our corpus consists of a set of data: (i) discourses about the proofreading practices, putted into circulation in different spaces, such as foruns and specific courses for professional readers; (ii) texts relating to text revision practices in a Facebook community called Reviewers; and (iii) notes from editorial Co-enunciator engaged in a process of editing a distance learning textbook. The discussion is based on the theoretical concepts developed by Dominique Maingueneau (2008, 2010) in order to apprehend the Discursive machinery as enunciation scenes that implies a discursive ethos. It allows us to analyze the discursive place occupied by the editorial mediators, looking for the figure of text reviewer. Considering this issue, we also investigate, through the notion of editorial genetic rites proposed by Salgado (2011), the historical, opaque and heterogeneous conditions of the linguistic material with the text reviewer works. The theoretical and methodological guidelines are justified as far as the reflections leads us to a collective complexity, connecting different places and memories, revealing the central position of proofreading activity the publishing.